The Perpetuation of a Myth: The Anderson-Axworthy Affair - Sisler, Berenice B. (Atlantis, 2015)
A member of the Canadian Advisory Council on the Status of Women (CACSW) gives her account of events comprising the crisis of 1980-81. As an activist from outside Ontario, Berenice Sisler presents a different view than that of lawyers and the central Canadian women’s movement. Sisler indicated that this account was written in 1997. She referred to Edward Greenspon and Anthony Wilson-Smith (1996) as having provoked it, and wrote in ink at the bottom of the last page “February, 1997.”